Wild Edible Mushrooms: Non-wood forest Products for Livelihood Generation - Das, Nilanjana; Mahapatra, S. C.; Chattopadhyay, R. N. (Indian Forester, 2002)
Wild mushrooms are important Non-Wood Forest Products (NWFP) from the forests and are being used as food since prehistoric times. About 280 species of edible mushrooms are available in the forests of India. Such mushrooms are protein rich and some of them are mycorrhizal, found on trees, while others are non-mycorrhizal. In Himachal Pradesh, about 70 edible mushrooms belonging to different species have been identified. Important species have been briefly described, indicating regions where these are found. Very few of these wild edible mushrooms have been commercially exploited. A good many of these can be collected and consumed as vegetables. They form part of the diet of the local tribal people but are generally neglected in urban civilized society owing to ignorance of their food value and panic about poisonous effects. Awareness about their food value should be created as these are quite tasty. On the other hand, popularized flowers mushroom packing has reduced their number and. Careful study of this effect is needed. Efforts should also be made to maintain their genetic variability in their natural habitat.